The Analysis of HOTS (Higher Order Thinking Skills) Questions Based on Brookhart Category in the 2013 Curriculum High School Chemistry Textbook - Lia Agustina; Tonih Feronika; Luki Yunita (Chemistry Education Department, 2021)
Higher Order Thinking Skills is one of the skills necessary in 21st century. So, learning media are required to improve students’ higher order thinking skills. Chemistry textbooks which are used as learning media should contain questions that improve students' thinking processes, especially higher order thinking skills (HOTS). However, there are no criteria for assessing the questions in the textbook, especially for higher order thinking questions. This study aims to determine the HOTS aspect using the Brookhart category on questions contained in the XII grade chemistry textbook. The research method used is descriptive method of document analysis. The results showed that the average percentage of HOTS questions in the three class XII chemistry textbooks was 25.95%, covering aspects of analyzing 8.85%, creating 3.51%, reasoning and logic 8.35%, problem solving 3.71%, and creative thinking 1.53%. Meanwhile, the aspects of evaluating and making decisions are not present in each analyzed chemistry textbook. Based on the research results, it can be seen that the chemistry textbook for class XII is still dominated by questions of low-level thinking skills.